Sosialisasi Penyusunan Laporan Keuangan Pada Depot Air Minum Isi Ulang Mhafa - Shinta Bella; Nike Apriyanti; Hari Sriwijayanti (Konsienti : Community Services Journal, 2023)
This community service is proposed to caary out activities that are socialization and education in one of the micro, small and medium enterprises in the Mafha Refill Drinking Water Depot business on Jl. Tanah Sirah Kec. Lubuk Begalung Padang, West Sumatera. This activity is proposed to socialize the importance of increasing knowledge and understanding of preparing financial reports for micro, small and medium enterprises, which is relate to assistance in preparing financial reports in the form of compiling a trial balance at the beginning of the period, compiling a profit and loss report, compiling a balance sheet at the end of the period. The activity implematation method consists of five stages. The first stage of preparation includes pre-survey. The second stage is the screening stage. The third stage is the activity implementation stage. Provide material on the preparation of financial reports and assistance in the preparation of financial reports. Evaluation is carried out by camparingthe conditions of the patners before and after the implementation of the program using interview and observation methods. After that, a report is prepared for further publication.